Islam dan Gaya Hidup Minim Sampah (Zerowaste lifestyle): Telaah Konsep Ecosophy Sayyed Hossein Nasr - Qinthary Hawwi Al-Adawiyah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss Islam and minimum waste lifestyle: the concept of ecosophy by Sayyed Hossein Nasr. This research uses a qualitative approach by applying library study methods. The formal object of this research is the concept of Sayyed Hossein’s ecosophy, while the material object is Islam and minimal waste lifestyle (zerowaste lifestyle). The results and discourse in this study show that there is a misconduct against nature done by man so that he causes damage to nature and ultimately affects man himself. Therefore, there needs to be a return to human understanding of nature with the concept of ecosophy Sayyed Hossein Nasr, who states that man is not one—the only creature that cares about the world. The research concludes that the Zerowaste lifestyle concept is an implementation of Sayyed Hussain Nasr’s ecosophy theory about the human Khalifatullah who has the task of innovating in environmental conservation and care using the 5R principle, which means refuse, reduce, reuse, recycle, and rot. The principle is made with the aim of restoring nature as a subject to be protected, not as an object that can be exploited.